Kepribadian Tokoh dalam Naskah Drama Mega-Mega Karya Arifin C. Noer: Kajian Psikologi Sastra: Character's Personality In The Play Mega-Mega By Arifin C. Noer: A Study Of Literaly Psychology - Lusiana, Meyta; Sadida, Arina; Putri, Ristin Dwi; Meliani, Niken; Wariyanti, Endang (Universitas Tidar, 2025)
This study examines the personality of the characters in the play Mega-Mega by Arifin C. Noer through a literary psychology approach with Sigmund Freud's psychoanalysis theory, which includes id, ego, and superego. This study aims to understand the psychological dynamics of the characters in the drama as well as how intrinsic elements such as theme, character, characterization, setting, mandate, and language style support the representation of inner conflict and social reality. Using a descriptive qualitative method, data were collected through documentation techniques from the dialog, actions, and monologues of the characters in the script. The analysis showed that characters such as Mae, Retno, Panut, Koyal, Tukijan, and Hamung reflect different personality structures. Mae shows the dominance of the superego with her loving motherhood, while Retno is dominated by the id through her impulsiveness and anger. Panut displays the ego in his attempt to balance desire and reality, while Koyal is trapped in the illusions of the id. Tukijan and Hamung display stubbornness and cynicism respectively, reflecting ego and superego. The theme of alienation and social inequality strengthens the psychological portrayal of the characters, supported by the setting such as the square and the bitter atmosphere that enlivens the narrative. This study concludes that Mega-Mega not only presents social conflicts, but also the psychological complexity of humans grappling between instinctive urges, logic, and morality, reflecting the reality of life in marginalized communities.